(untitled) (Applied Biological Research, 2023)
The skin colour of potato tubers is one of the most noticeable visual characteristics and ranges from white-cream to black in appearance. A study was conducted to understand tuber skin colour variation in potatoes using contrasting parents. A set of 327 segregating progenies of 8 populations, developed by using ‘CP 4242’ as female (2 crosses) and male (6 crosses) were assessed for tuber skin colour. Based on the presence or absence of colour, the segregating progenies were classified into 5 skin colours viz., white-cream, light red, dark red, light purple and dark purple with the help of potato colour chart. The 327 segregating progenies of 8 crosses exhibited a prevalence of 137 (41.9%), 71 (21.7%), 12 (3.7%), 17 (5.2) and 90 (27.5%) in dark purple, light purple, dark red, light red and white-cream tuber skin colours, respectively. In totality 72.48% progenies possessed coloured tuber skin (dark purple, purple, dark red and light red) as compared to 27.52% progenies exhibiting white-cream skin colour, reflecting 3:1 segregation ratio of tuber colour variation in potato breeding population. This reveals the dominance of purple colour over white in the segregating population.